2018
DOI: 10.2337/cd17-0063
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers’ Perceptions of Responsibilities and Resources to Reduce Type 2 Diabetes Risk After Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) increases the risk for type 2 diabetes. This qualitative study aimed to evaluate health care providers' perceptions of care responsibilities and resources related to reducing type 2 diabetes risk among women with previous GDM in Singapore. Health care providers acknowledged a shared responsibility. They felt that they had less understanding of compliance with long-term maintenance of lifestyle change, exacerbated further by fragmentation of follow-up care. The application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…‘No proper system to identify and retain patients in the current care model.’ (primary care clinician) 21 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…‘No proper system to identify and retain patients in the current care model.’ (primary care clinician) 21 …”
Section: Resultsmentioning
confidence: 99%
“… 20 Singaporean participants contrasted their system to the Australian one, where a national registry of patients facilitated systematic follow-up. 21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fok et al also reported that Chinese mothers (83.7%) were least likely to bring their child outside the home compared to Indians (79.9%) and Malays (66.1%) ( 27 ). If possible, mothers can consider seeking help in looking after their child from their parents, in-laws, spouses, siblings, or even trusted neighbors while they attend their postnatal physician visits ( 28 ). Public and social policies such as paternity leave for fathers ( 29 ) or encouraging young families to stay near to their parents through housing incentives ( 30 ) may also help to address this barrier.…”
Section: Discussionmentioning
confidence: 99%